RESPON KELANGSUNGAN HIDUP DAN PERTUMBUHAN LARVA TERHADAP PADAT TEBAR IKAN TAMBAKAN (Hellostoma temmincki. C.V) - Muhammad Sugihartono; David David (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
Fish Tambakan (H. temmincki. CV) is one of the freshwater fish species from the tropics, precisely Southeast Asia. Currently the presence of fish gouramis (H. temmincki. CV) already scarce, and threatened that should be preserved. One effort that can be done to preserve this fish is through cultivation, Density is closely related to the production and the expected growth rate of fish. Activities carried out for 5 months, in hectery Fish Seed Center (BBI) Tempino, District Mestong, Kabupten Muaro. Test fish are fish larvae Tambakan (H. temmincki. CV) of 71 400 individuals. The container used is aquarium measuring 42.5 x 40 x 40 cm, with a height of 10 cm of water as much as 12 aquariums. This research is a design environment completely randomized design (CRD) with 4 treatments and 3 Deuteronomy. The results of this study to the best stocking density is treatment A (200 individuals / liter) which resulted in the percentage of survival of the highest of 86.21%., Average length and weight growth - average yield growth of average length - average 1.50 cm / tail and average weight - average 0159 g / tail and average daily growth - average 0.00396 grams / tail.Keywords: Kissing gourami (Hellostoma temmincki. CV), Solid stocking